Pengaruh Pemberian Tepung Kiambang (Salvinia molesta) Terfermentasi dalam Ransum terhadap Performa Ayam Jawa Super (Joper) - H Angelina; N Nurhayati; A A Candra (PETERPAN (Jurnal Peternakan Terapan), 2021)
This study aims to analyze the effect of giving fermented kiambang ( Salvinia molesta) flour on the performance of super Javanese chicken (joper) the research was conducted at the Lampung State Polytechnic enclosure. As many as 100 joper chickens are kept. Experimental research, using two treatments, namely for control 100% commercial feed and the second treatment with 10% fermented kiambang flour. This result does not affect the performance on the joper chickens. This can be seen from the data on ration consumtion, body weight gain, ration conversion, and mortality. However, fermented kiambang can be used as an alternative as a commercial feed mixture.the weight of the hen given the 10% kiambang is 734, 16 g